2018
DOI: 10.1111/jppi.12239
|View full text |Cite
|
Sign up to set email alerts
|

Current Representation of People With Intellectual Disability in Australian Mental Health Policy: The Need for Inclusive Policy Development

Abstract: People with intellectual disability in Australia experience poor mental health, are underrepresented in mental health policy, and encounter major barriers in accessing mental health services and treatments. This study interrogated the current representation of people with intellectual disability and recommended strategies to enhance the inclusion of intellectual disability in mental health policy. A policy analysis framework was developed that included context, stakeholders, process, and content. Nine pieces o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…Specific consideration of people with ID in Australian mental health policy is missing. This is a significant exclusion, given the very high rate of mental illness of up to 50%,5 9 reflecting and contributing to major barriers in access to mental health services and treatments 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Specific consideration of people with ID in Australian mental health policy is missing. This is a significant exclusion, given the very high rate of mental illness of up to 50%,5 9 reflecting and contributing to major barriers in access to mental health services and treatments 10 11…”
Section: Introductionmentioning
confidence: 99%
“…Despite ratification of the UNCRPD and duties to involve service users, policy influence by people with a learning disability is limited (Robinson and Chenoweth, 2011). Although some progress has been made, people with a learning disability continue to be generally under-represented in politics and policymaking, even when the focus is disability (Dew et al, 2018;Irvine, 2017).…”
Section: Disability Rights and Policymentioning
confidence: 99%
“…Indeed, Australian intellectual disability mental health policy falls short of its obligations under the UN Convention on the Rights of Persons with Disabilities (UNCRPD) and lags behind leading international standards in intellectual disability health policy. A recently published in-depth analysis and review of current Australian mental health policy to assess the representation of people with intellectual disability by our group (Dew et al, 2018) found limited inclusion of this population. We identified 37 relevant mental health policy documents and less than half of these documents mentioned people with intellectual disability.…”
mentioning
confidence: 90%
“…The estimated prevalence of intellectual disability is about 1-2% of the population (Australian Institute of Health and Welfare [AIHW], 2003), yet the mental health needs of this minority group are substantial. Across the lifespan, people with intellectual disability exhibit vulnerability to common mental disorders, with an estimated 30-50% experiencing mental illness (Einfeld et al, 2011). Notably, people with intellectual disability are two to three times more likely than the general population to develop schizophrenia, and its onset occurs earlier than for other Australians.…”
mentioning
confidence: 99%